2017
DOI: 10.1101/190835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Out-of-Register Aβ42Assemblies as Models for Neurotoxic Oligomers and Fibrils

Abstract: ABSTRACT:We propose a variant of the recently found S-shaped Aβ 1−42 -motif that is characterized by out-of-register C-terminal β-strands. We show that chains with this structure can not only form fibrils that are compatible with the NMR signals, but also barrel-shaped oligomers that resemble the ones formed by the much smaller cylindrin peptides. Running at physiological temperatures long all-atom molecular dynamics simulations with an explicit solvent, we study the stability of these constructs and show that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Combining IM/MS, EM, AFM and computational modeling, the Eisenberg's group 457 demonstrated that cylindrin-like barrels of tandem repeats of Aβ fragments with a length of 11 residues (residues 24-34, 25-35, 26-36) held together by two glycine residues are stable. To check whether a similar structure is possible for Aβ oligomers, Xi et al 458 built out-of-register Aβ42 assemblies and also discovered barrel-shaped structures consisting of β2-turn-β3 domains (residues 27-42). They occurred both in trimers and in tetramers, though the stability in the latter is higher than in the former after at least 200 ns of MD simulations with explicit water.…”
Section: A B D Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining IM/MS, EM, AFM and computational modeling, the Eisenberg's group 457 demonstrated that cylindrin-like barrels of tandem repeats of Aβ fragments with a length of 11 residues (residues 24-34, 25-35, 26-36) held together by two glycine residues are stable. To check whether a similar structure is possible for Aβ oligomers, Xi et al 458 built out-of-register Aβ42 assemblies and also discovered barrel-shaped structures consisting of β2-turn-β3 domains (residues 27-42). They occurred both in trimers and in tetramers, though the stability in the latter is higher than in the former after at least 200 ns of MD simulations with explicit water.…”
Section: A B D Cmentioning
confidence: 99%
“…The stability of tetrameric Aβ40 and Aβ42 β-barrel structures, which are different from out-of-register barrels, 458 was probed by REMD simulation with four atomistic force fields. 459 In aqueous solution, due to a change in the CHC-CHC and C-end-C-end interfaces, a β-barrel structure, made of eight antiparallel β-strands covering residues 9−40/42 with two distinct β-hairpin types and an inner pore diameter of 0.7 nm, exists transiently and to a greater extent for Aβ42 than Aβ40.…”
Section: A B D Cmentioning
confidence: 99%